Differential DNA methylation in infants with IgE- and non-IgE-mediated cow’s milk allergy and its association with acquired tolerance - López-Gómez, Rebeca; Gil-Martínez, Marta; Ladrón-Guevara, Ana; Rodrigo-Muñoz, Jose Manuel; Lorente-Sorolla, Clara; Rodríguez-González, Daniel; García de Castro, Zahara; Guillén-Sánchez, Gema; Serrano-Santiago, Antonio; Mirasierra-Pérez, Raquel; Cañas, José Antonio; Del Río Camacho, Genoveva; et al. (Frontiers in Immunology, 2025)
BackgroundCow’s milk allergy (CMA) is one of the most common food allergies (FA) in childhood. This condition can be IgE-mediated, non-IgE-mediated, or a combination of both. Diagnosis involves clinical history in conjunction with sensitization tests. However, these tests have limited predictive value, making the oral food challenge (OFC) the gold standard for diagnosis. Recent research has focused on identifying biomarkers, including DNA methylation patterns, for FA diagnosis. The aim of this study is to investigate the differences in DNA methylation associated with distinct patterns of CMA, to identify new diagnostic biomarkers.MethodsGenome-wide DNA methylation profiling was performed on blood samples from infants with IgE-mediated CMA (CMAIE), non-IgE-mediated CMA (CMANIE), and non-allergic controls, at baseline and after 6 months of an exclusion diet in CMA groups. These results were then correlated with tolerance acquisition following the restrictive diet.ResultsA total of 19 infants were enrolled (10 CMAIE, 6 CMANIE, and 3 controls). Significant differentially methylated regions (DMRs) annotated to both genes and promoters were identified in all groups, and a clear separation of the samples into their respective groups was observed. Furthermore, DMRs in promoters and genes were identified in tolerant CMAIE children after the exclusion diet, being associated to tolerance.DiscussionDifferential DNA methylation in CMA children is a useful diagnostic biomarker, and it could also be valuable in predicting the resolution of such pathologies.